Quantitative description of low-cycle fatigue damage accumulation in contact interaction zone by local strain evolution - Sviatoslav Eleonsky; Yury Matvienko; Vladimir Pisarev; Igor Odintsev (Fracture and Structural Integrity)
The novel non-destructive method for quantitative description of low-cycle fatigue damage accumulation is expanded to a case of contact interaction in the stress concentration area. Investigated objects are plane aluminium specimens with the centred hole filled by cylindrical steel inclusion. The specimen is subjected to cyclic pull-push loading. The key point, that defines scientific novelty and powerfulness of the developed approach, consists of involving local deformation parameters as current damage indicators. Required strain values follow from distributions of all three displacement components along the filled hole edge measured by reflection hologram interferometry. The data, which are derived at different stages of low-cycle fatigue for the single specimen, provide normalized dependencies of local strain values from number of loading cycle, which are a source of damage accumulation functions. These functions are constructed for the specimen with the filled hole and geometrically analogous specimen with the open hole. Obtained data quantitatively describe a difference in damage accumulation rates for two cases.